1997
DOI: 10.1007/pl00007566
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Type II Soluble Tumor Necrosis Factor Receptors in the Bronchoalveolar Lavage Fluids of Patients with Sarcoidosis

Abstract: Since tumor necrosis factor (TNF) is known to be involved in granuloma formation in sarcoidosis, and soluble TNF receptors (sTNF-Rs) inhibit TNF action in vivo, we evaluated the levels of sTNF-Rs in the bronchoalveolar lavage fluids (BALF) of 31 subjects using an enzyme-linked immunosorbent assay. Our group consisted of 13 patients with sarcoidosis (7 sarcoidosis patients who received no treatment and 6 who received corticosteroid therapy) and 18 control subjects (11 healthy nonsmokers and 7 asymptomatic smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…Increased levels of TNF-Rs have been seen in the plasma and BAL fluid of patients with sarcoidosis. 11 Armstrong et al 12 showed that TNFα bioactivity in the lungs of subjects with sarcoidosis may be inhibited by increased levels of soluble TNF-R. This inhibition may be greater in stage I disease than in stage II/III, indicating a homeostatic mechanism which protects the lung from excessive TNFα production.…”
Section: -5mentioning
confidence: 99%
“…Increased levels of TNF-Rs have been seen in the plasma and BAL fluid of patients with sarcoidosis. 11 Armstrong et al 12 showed that TNFα bioactivity in the lungs of subjects with sarcoidosis may be inhibited by increased levels of soluble TNF-R. This inhibition may be greater in stage I disease than in stage II/III, indicating a homeostatic mechanism which protects the lung from excessive TNFα production.…”
Section: -5mentioning
confidence: 99%
“…Serum TNF-␣ and plasma sTNF-R55 and sTNF-R75 concentrations were measured in duplicate with enzyme-linked immunosorbent assay (ELISA) kits (Quantikine; R&D Systems, Minneapolis, MN) (23,24). Briefly, a microtiter plate was coated with a murine monoclonal antibody specific for TNF-␣ , sTNF-R55, or sTNF-R75.…”
Section: Determination Of Serum Tnf-␣ and Plasma Stnf-r Levelsmentioning
confidence: 99%
“…Serum TNF-␣ and plasma sTNF-R55 and sTNF-R75 concentrations were measured in duplicate with enzyme-linked immunosorbent assay (ELISA) kits (Quantikine; R&D Systems, Minneapolis, MN) (31). Briefly, a microtiter plate was coated with a murine monoclonal antibody specific for TNF-␣ , sTNF-R55, or sTNF-R75.…”
Section: Determination Of Serum Leptin and Tnf Levelsmentioning
confidence: 99%